Comparative genomics and concerted evolution of beta-tubulin paralogs in Leishmania spp. - Jackson, A; Vaughan, S; Gull, K (BioMed Central, 2006)
BACKGROUND: Tubulin isotypes and expression patterns are highly regulated in diverse organisms. The genome sequence of the protozoan parasite Leishmania major contains three distinct beta-tubulin loci. To investigate the diversity of beta-tubulin genes, we have compared the published genome sequence to draft genome sequences of two further species L. infantum and L. braziliensis. Untranscribed regions and coding sequences for each isoform were compared within and between species in relation to the known diversity of beta-tubulin transcripts in Leishmania spp. RESULTS: All three beta-tubulin loci were present in L. infantum and L. braziliensis, showing conserved synteny with the L. major sequence, hence confirming that these loci are paralogous. Flanking regions suggested that the chromosome 21 locus is an amastigote-specific isoform and more closely related (either structurally or functionally) to the chromosome 33 'array' locus than the chromosome 8 locus. A phylogenetic network of all isoforms indicated that paralogs from L. braziliensis and L. mexicana were monophyletic, rather than clustering by locus. CONCLUSION: L. braziliensis and L. mexicana sequences appeared more similar to each other than each did to its closest relative in another species; this indicates that these sequences have evolved convergently in each species, perhaps through ectopic gene conversion; a process not yet evident among the more recently derived L. major and L. infantum isoforms. The distinctive non-coding regions of each beta-tubulin locus showed that it is the regulatory regions of these loci that have evolved most during the diversification of these genes in Leishmania, while the coding regions have been conserved and concerted. The various loci in Leishmania satisfy a need for innovative expression of beta-tubulin, rather than elaboration of its structural role.